2012
DOI: 10.1159/000339578
|View full text |Cite
|
Sign up to set email alerts
|

Get With The Guidelines Stroke Performance Indicators in a Brazilian Tertiary Hospital

Abstract: Background: Stroke is the fourth leading killer in the US, the first in Brazil and a leading cause of adult long-term disability in both countries. In spite of widespread recommendation, clinical practice guidelines have had limited effect on changing physician behavior. Recognizing that both knowledge and acceptance of guidelines do not necessarily imply guideline adherence, the American Heart Association/American Stroke Association (AHA/ASA) developed a national stroke quality improvement program, the ‘Get W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 42 publications
3
16
0
Order By: Relevance
“…For the in-hospital treatment KPIs, two important factors related to mortality and disability after stroke were evaluated, venous thromboembolism prophylaxis and antithrombotic therapy. These reached approximately 90% in both the centers, which was very similar to the previously reported national and international data 15,16 .…”
Section: Discussionsupporting
confidence: 91%
“…For the in-hospital treatment KPIs, two important factors related to mortality and disability after stroke were evaluated, venous thromboembolism prophylaxis and antithrombotic therapy. These reached approximately 90% in both the centers, which was very similar to the previously reported national and international data 15,16 .…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with this idea, this study observed that adherence to the GWTG-S quality indicators was lower in patients with TIA. This difference has also been reported in the United States [6][7][8][9] . This is a systematically underestimated, alarming finding, especially because a TIA comprises a major risk factor for further stroke.…”
Section: Discussionsupporting
confidence: 72%
“…All measures indicate the proportion of eligible patients (those without documented reasons for non-treatment) who received the intervention described 7 . A composite measure score of performance was calculated by summing the numerators for each measure across the patients evaluated to create a composite numerator (all the care that was given), summing the denominators for each measure to form a composite denominator (all the care that should have been given), and reporting the ratio of all the needed care that was given.…”
Section: Measurement Of Quality Indicatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…the Canadian Stroke Network 14 . In more recent years, improvements in acute stroke care and prevention have led to a decrease in stroke mortality and stroke incidence 15,16,17 .…”
Section: Endovascular Reperfusion Therapymentioning
confidence: 99%